(untitled) - Edwards, Sheila (New York, NY., 2005)
Literature for Lively Lessons supplies teachers with age-appropriate reading lists for children in pre-K through third grade. Organized in a practical calendar format that ties in picture books with seasons, holidays, and other milestones, the book takes teachers, homeschoolers, and librarians beyond the tired old standards and introduces them to new books and fresh perspectives. Literature for Lively Lessons is thoroughly indexed and easy to use, so teachers can spend less time planning and more time actually teaching
Keywords: Children's literature,Lesson planning,Children,Calendars,Picture books for children; Study and taching ( primary ),Books and reading; United States,United States,United States,United States,United States